Biotic and Abiotic Decomposition of Indeno-Pyrene and Benzo(GHI) Perylene in Sewage Sludge under Various Light Conditions = Biotyczny i abiotyczny rozpad indeno-pirenu i benzo(ghi)perylenu w różnych warunkach świetlnych - Włodarczyk-Makuła, Maria; Wiśniowska, Ewa; Popenda, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the studies was to determine the changes in the concentration of PAHs in sewage sludge stored under various light conditions. The sewage sludge samples were stored under aerobic conditions. Sewage sludge samples were deposed in darkness, in laboratory conditions and exposed to UV rays.
Keywords: sewage sludge; PAHs; GC-MS; darkness; daily light; UV rays; osady ściekowe; WWA; światło dzienne; promienie UV